The Enhancement of Student Learning Engagement in EFL Speaking Flipped Classrooms - Zhong, Linling (Transactions on Social Science, Education and Humanities Research, 2024)
Student learning engagement plays an essential role in learning, and it is a valuable factor for effective learning. Meanwhile, in English as a foreign language (EFL), speaking is one of the critical competencies for students. Scholars and educators are looking for a breakthrough to effectively improve student learning engagement and EFL speaking. With the advancement of information and communication technologies developing, the flipped classroom is a new tendency in today’s education and has been proven to be effective. The application of flipped classrooms is the field of study in which this work looks to make a breakthrough. Nevertheless, little research has been undertaken to consider student learning engagement in EFL speaking flipped classrooms rigorously. Furthermore, no review studies have given the task of clarifying the interrelationships between student learning engagement and EFL speaking flipped classrooms enough attention. Therefore, based on this background, this review aims to review and explore the enhancement of EFL speaking flipped classrooms on student learning engagement, highlighting the positive connection between these valuable constructs. Finally, practical ramifications and directions for students, instructors, and course developers interested in implementing flipped classrooms to improve student learning engagement and EFL speaking are presented.